(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2014)
The article refers to the myth of possible disappearance of borders (state, national and ethnical borders). The author compares the theories of two eminent anthropologists Victor Turner and Frederik Barth which contain the concept of liminality while researching sensitive aspects of society where man is facing the borders or limitations.